NGO contributions to the economic development in selected areas of Iloilo - Almalbis, Kristy G.; Fuene, Loraine K.; Solis, Jonalyn S.; Suelo, Leah Mae B.
Executive summary - Government agencies have different functions in the society to promote cannot do it alone. It needs the cooperation and dedication of concerned citizens. People should support government's plans for economic development until its completion. Non-Government Organizations (NGOs) are more concerned on leadership, social interaction and economic development. Through their economic projects, some people were employed and others are learning and adopting business tools and techniques in doing projects. This study deals with the contribution of NGO to the economic development in selected areas of Iloilo. The interviews to the heads and other concern people contribute to the completion of this study. Based on the information and dat gathered, NGO helped the government fulfill its goal to the society and to the people. They conctribute to the development, not only in economic aspect, as well as in social and moral life of the people. NGO focused on different areas of living. They helped people develop their talents, skills and initiatives that will be useful in their daily living. Through training, workshops, awareness and forum, people were able to elevate their standards of living. NGO contribution to economic aspect was minimal but cannot be ignored. NGO was important in the fulfillment of economic development plan of the government.